1992
DOI: 10.1161/01.hyp.20.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Increased systolic pressure in chronic uremia. Role of arterial wave reflections.

Abstract: To assess the role of arterial wave reflections in the mechanism of systolic hypertension and altered pulsatile arterial dynamics in patients with end-stage renal disease (ESRD), 79 ESRD patients were compared with 73 age-matched control subjects with normal renal function and similar mean blood pressure. Wave reflections were investigated from the carotid pulse contour recorded by applanation tonometry using a Millar micromanometer-tipped probe. Wave reflections were quantified as the ratio (augmentation inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
0
13

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(156 citation statements)
references
References 38 publications
6
137
0
13
Order By: Relevance
“…The association of increased education level with a better quality of life has also been represented by greater income levels and was also found in this study (data not shown). Pulse pressure remained an independent contributor to the PCS score and is an indirect measure of vascular compliance that is altered in the hypertensive state and in individuals with renal insufficiency (27). Pulse pressure may represent more severe disease in ADPKD individuals with renal insufficiency and hypertension (1).…”
Section: Discussionmentioning
confidence: 99%
“…The association of increased education level with a better quality of life has also been represented by greater income levels and was also found in this study (data not shown). Pulse pressure remained an independent contributor to the PCS score and is an indirect measure of vascular compliance that is altered in the hypertensive state and in individuals with renal insufficiency (27). Pulse pressure may represent more severe disease in ADPKD individuals with renal insufficiency and hypertension (1).…”
Section: Discussionmentioning
confidence: 99%
“…The time to return of the reflected wave (Tr) was calculated as the time from the beginning of the derived aortic systolic pressure waveform to the inflection point. Tr can be used as a substitute for pulse wave velocity (a higher pulse wave velocity will result in a shorter Tr) (London et al, 1992). Subjects were studied after a minimum 12-h fast in the morning between 0700 to 1000 hours and were asked to refrain from alcohol consumption and heavy exercise on the day before measurements.…”
Section: Arterial Stiffnessmentioning
confidence: 99%
“…Therefore, T i is used as an indicator of aortic PWV and AS, since it has been shown that there is very good association between these parameters. [22][23][24] It should be mentioned that the T i is a surrogate of aortic PWV and there are no studies that have definitively shown the clinical significance of this marker. The PPP/CPP ratio depends on both arterial wall properties and pressure augmentation from the reflected wave.…”
Section: Pulse Wave Analysismentioning
confidence: 99%
“…The former relates to coronary flow during diastole whereas the latter is an index of systolic stress relating to oxygen demand. 24 The SEVR gives information about the balance between oxygen demands and endocardial blood flow. 25 The PRP, which refers to the product of SBP and HR during exercise, is a good measure of myocardial oxygen uptake 26 and it depends on exercise intensity.…”
Section: Pulse Wave Analysismentioning
confidence: 99%